PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENYELUNDUPAN PAKAIAN BEKAS DI TINJAU MENURUT UNDANG-UNDANG NOMOR 7 TAHUN 2014 TENTANG PERDAGANGAN - Tri Agung Riono (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTUsed clothing is now a product that is often sought by various circles masyarakat.Mereka who choose these items have a variety of reasons that vary, there are assuming that imported goods have a better quality, some also want to have it because the price of these items more affordable. Then, what's so great about that used clothes? Why is it reaching into society regardless of age? And if there is danger of the used clothes, we all know that our domestic products are difficult to compete with foreign products, especially coupled with the government's policy of free trade with China and ASEAN in 2015, of course our products will be increasingly lost only in terms of quality , creativity, innovation, up to the price. Not only new items imported but used goods imported including clothing. According to data from the Ministry of Industry of the Republic of Indonesia in the 1st quarter of 2013 there are about 112 containers containing used clothing and all, the goods do not have the complete illegal aliases, which come from all Indonesian ports, mostly through port in Pekanbaru Riau we know Kemenperin banned from imported used clothes since 2003 ago. Import and Export activities are not separated by the laws and regulations. Since the beginning of export and import activities have been regulated in the legislation until now there are still applicable to those that have not been valid or have changed. In order to realize the rules of legislation based on Pancasila and the 1945 Constitution, which contained the principles of justice, upholds the right of every member of society, and places Customs Obligations as state obligations reflecting the participation of community members in collecting funds through payment of import duty , then came the Law Number 10 Year 1995 About Customs. Law Number 17 Year 2006 regarding Amendment to Law Number 10 Year 1995 regarding Customs. Law No. 17 of 2006 does not alter the full content of the previous law, but there are several Articles that have been deleted and added to the content of the law. In addition to the emergence of Law Number 10 Year 1995, there are also derivatives of this legislation, namely the Decree of the Minister of Industry and Trade No. 230 / MPP / Kep / 7/1997 on goods subject to import trade regulation. This regulation appears as an explanation of the contents of Law Number 10 of 1995. This minister's decision to impose restrictions on imported goods that may enter the territory of the Republic of Indonesia. This is done so as not to be a loss to the trade industries in Indonesia.Keywords: Used Clothing, Trade, Customs